Deductive reasoning with factual, possible and counterfactual conditionals - BYRNE, RUTH MARY JOSEPHINE (Psychonomic Society, 1999)
We compared reasoners' inferences from conditionals based on possibilities in the present or the past (e.g., "If Linda had been in Dublin then Cathy would have been in Galway") with their inferences based on facts in the present or the past (e.g., "If Linda was in Dublin then Cathy was in Galway"). We propose that people construct a richer representation of conditionals that deal with possibilities rather than facts: Their models make explicit not only the suppositional case, in which Linda is in Dublin and Cathy is in Galway, but also the presupposed case, in which Linda is not in Dublin and Cathy is not in Galway. We report the results of four experiments that corroborate this model theory. The experiments show that reasoners make more inferences from conditionals based on possibilities rather than on facts when the inferences depend on the presupposed case. The results also show that reasoners generate different situations to verify and falsify conditionals based on possibilities and facts.
PUBLISHED
Keywords: Psychology